The discount version of large deviations for a randomly indexed sum of random variables - Kasparavičiūtė, Aurelija; Saulis, Leonas (Lietuvos matematikos rinkinys, 2011)
In this paper, we consider a compound random variable Z = \sum^N_{j=1} vjXj , where 0 < v < 1, Z = 0, if N = 0. It is assumed that independent identically distributed random variables X1,X2, . . . with mean EX = μ and variance DX =σ2 > 0 are independent of a non-negative integer-valued random variable N. It should be noted that, in this scheme of summation, we must consider two cases: μ eq 0 and μ = 0. The paper is designatedto the research of the upper estimates of normal approximation to the sum ˜ Z = (Z −EZ)(DZ)−1/2, theorems on large deviations in the Cramer and power Linnik zones and exponential inequalities for P( ˜ Z > x).
Keywords: cumulant; large deviations theorems; discounted limit theorems; normal approximation; random number of summands